Precariedade no ciberjornalismo: o caso dos jornais transmontanos - Ferrador, Susana (2019)
There is more and more information circulating in a network. We live in a global age where everything seems to be close and where new technologies play a nearly ubiquitous role. In this era in which globalization and individualization are very close, interest in everything that is local has grown, revealing, as never before, regional cyberjournalism. The regional media are bastions of identity, affinity and memory of the communities that are close to them and their importance is unquestionable. It is precisely because of this importance that we set out to look at the media in the region of Trás os Montes, namely those that are registered in the districts of Bragança and Vila Real, presenting the mapping of what currently exists and analyzing descriptively, based on the consultation of the records techniques of online newspapers, the current number of journalists with a professional or trainee portfolio, who works in the Transamerican newsrooms. The findings reveal a very high number of contributors to newsrooms that do not have a professional license and a very small number of journalists. In a region with very specific social and demographic characteristics that distinguish it from the national panorama, and where the editorial criteria and the form of making journalism often happens by "orders" of news from the population of the respective towns or villages where they are inserted these data can reinforce the precariousness and sedentary lifestyle that is being experienced by all the online newsrooms in the country, but especially those from the interior, which struggle daily with economic constraints, adversity that has a direct effect on quality and credibility of what is reported.